Consolidation with autologous stem cell transplantation in first remission is safe and effective in AML patients above 65 years. (February 2017) - Heini, Alexander D.; Berger, Martin D.; Seipel, Katja; Taleghani, Behrouz Mansouri; Baerlocher, Gabriela M.; Leibundgut, Kurt; Banz, Yara; Novak, Urban; Pabst, Thomas
Graphical abstract: Elderly AML patients above 65 years derive similar benefits in overall survival from ASCT consolidation in CR1 as AML patients below 65 years. Highlights: The outcome of AML patients ≥65 years remains disappointing. Consolidation with autologous transplantation is feasible in elderly AML patients. ASCT consolidation in first remission provides longer PFS and OS in elderly AML. ASCT provides similar survival benefits in young and elderly AML patients. Abstract: The outcome of AML patients ≥65 years remains disappointing. Current post-induction strategies for elderly AML patients fit for intensive treatment involve additional cycles of chemotherapy or allogeneic transplantation. Consolidation with autologous transplantation (ASCT) is poorly studied in these patients. In this single-center retrospective analysis, we determined survival rates of AML patients ≥65 years undergoing busulfan/cyclophosphamide conditioning before ASCT in first remission between 2007 and 2015. We found elderly AML patients with ASCT to have longer progression-free survival (PFS; 16.3 vs. 5.1 months, P  = 0.0166) and overall survival (OS; n.r. vs. 8.2 months; P  = 0.0255) than elderly AML patients without ASCT consolidation. In addition, elderly AML patients undergoing ASCT had comparable PFS ( P  = 0.9462) and OS ( P  = 0.7867) as AML patients below 65 years receiving ASCT consolidation in CR1. Our data suggest that ASCT is an option in elderly fit AML patients who appear to benefit from autologous consolidation similarly to younger AML patients.